Construction of the phylogenetic tree of Pseudonitzschia sp.g3 isolated from haiphong city basing on the nucleotide sequence of the its1-5.8s-its2 gene fragment - Lan Anh, Hoang Thi; Hong, Dang Diem; Thuoc, Chu Van (Academia Journal of Biology, 2014)
Some species belonging to the marine diatom genus Pseudonitzschia were recognized to have capacity to produce domoic acid which caused amnesic shellfish poisoning (ASP). According to the traditional classification, researchers have relied on the morphological characters to identify the species of the genus Pseudonitzschia. In addition, the morphological study of the species belonging to the genus Pseudonitzschia were supported by phylogenetic analyses of the nuclear- encoded internal transcribed spacer 1-5.8S and the internal transcibed 2 rDNA (ITS1-5.8S-ITS2). In this study, the length of the ITS1-5.8S-ITS2 gene fragment of Pseudonitzschia sp.G3 was estimated about 825 bp. After, this fragment was amplified from Pseudonitzschia sp.G3 by using genomic DNA; the PCR products have been cloned into the pCRÒ2.1 vector and the recombinant plasmids were transformed into the E. coli strain DH5a T1’. The result of the cloning was confirmed by PCR checking method and the restriction analysis by EcoRI enzyme. By comparing the Pseudonitzschia sp.G3 nucleotide sequence with the published nucleotide sequences of the ITS1-5.8S-ITS2 gene fragments of Pseudonitzschia species in Gene Bank and constructing the phylogenetic tree, the phylogenetic relationships between Pseudonitzschia sp.G3 and 12 other Pseudonitzschia species were established. Our results indicated that Pseudonitzschia sp.G3 collected in Haiphong city had close phylogenetic relationship with Pseudonitzschia pungens (with accession number AY544769) with homological coefficient of 98.8%. The obtained results in this paper allowed us to conclude that may be the studied Pseudonitzschia sp.G3 species was Pseudonitzschia pungens.